Rancang Bangun Sistem Informasi Penjualan pada Rumah Makan - Achmad Sumbaryadi; Rahmat Hidayat; Riswandi Ishak; Siti Nur Khasanah (Faatuatua Media Karya, 2026)
The development of information technology has had a major influence on various business sectors, including the culinary and restaurant industry. Galiga Dramaga Restaurant still carries out sales processes and data management manually, resulting in recording errors, service delays, and difficulties in preparing sales reports. This study aims to design and develop a Sales Information System for the restaurant in order to make sales data management more effective and efficient. The research method used is the waterfall model with data collection methods including observation, interviews, and literature studies to obtain the data needed for system development. Meanwhile, the system development method uses the waterfall approach consisting of requirements analysis, system design, implementation, and system testing stages. The system is designed using UML modeling such as use case diagrams, activity diagrams, sequence diagrams, and Entity Relationship Diagrams (ERD). The results of the study indicate that the developed sales information system is able to assist in processing customer data, food menu data, ordering, payment transactions, and generating computerized sales reports. The system can also minimize data recording errors and accelerate customer service processes. Based on the testing results, the system can run properly according to user requirements and is able to support the operational activities of Galiga Dramaga Restaurant optimally. Therefore, this sales information system is expected to improve work effectiveness and service quality at Galiga Dramaga Restaurant.